2015
DOI: 10.1186/s13027-015-0012-2
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines against human papillomavirus in low and middle income countries: a review of safety, immunogenicity and efficacy

Abstract: Currently, there is limited data on the immunogenicity and efficacy of human papillomavirus vaccines in Low and Middle income countries (LMIC). The review aims to summarize the current status from published HPV vaccine safety, immunogenicity and efficacy studies in low and middle income countries (LMIC). Electronic databases (PubMed/MEDLINE and HINARI) were searched for peer reviewed English language articles on HPV vaccination in LMIC that have so far been published from 1st January 2006 up to 30th January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 37 publications
(101 reference statements)
1
18
0
Order By: Relevance
“…Where only as low as 10.2% of the participants have heard about HPV vaccines, 21.2 % reported having heard of cervical cancer, and the majority of these knew someone who had the disease. This result shows that the knowledge of HPV is somehow still low in many places, as this result is consistent with other low income and middle-income countries (25) . Masika et al reported that in Kenya the insufficient information about HPV vaccines is one of the main barriers to recommending the vaccine (26) .…”
Section: Knowledge Of Hpv Vaccinessupporting
confidence: 78%
See 1 more Smart Citation
“…Where only as low as 10.2% of the participants have heard about HPV vaccines, 21.2 % reported having heard of cervical cancer, and the majority of these knew someone who had the disease. This result shows that the knowledge of HPV is somehow still low in many places, as this result is consistent with other low income and middle-income countries (25) . Masika et al reported that in Kenya the insufficient information about HPV vaccines is one of the main barriers to recommending the vaccine (26) .…”
Section: Knowledge Of Hpv Vaccinessupporting
confidence: 78%
“…One strategy to reduce cost as discussed before is by reducing the dose from three-dose to twodose, with no change in immunogenicity (10) . As the two-dose strategy is said to be critically important to save resources on any extra dose administrated for lower and middle-income countries (25) . The support of government funding to make HPV vaccines as national health program is crucial, although, in reality, it is a difficult decision (31) .…”
Section: Cost and Affordabilitymentioning
confidence: 99%
“…High risk HPV DNA was determined 110 out of 328 patients (33.5%) and multiple types were detected 22.7% of the cases. The most determined types were HPV-16/51/18 and 56 respectively.…”
Section: Introduction High-risk Hpv Types In Cervical Cytologymentioning
confidence: 99%
“…6 Vaccine Safety have all confirmed and declared that the vaccine is safe and effective. [7][8][9] The FUTURE trials have demonstrated an efficacy of 91-100%.…”
Section: Introductionmentioning
confidence: 99%